Genome sequence of Oceanobacillus picturae strain S1, an halophilic bacterium first isolated in human gut. Issue 1 (December 2015) - Lagier, Jean-Christophe; Khelaifia, Saber; Azhar, Esam; Croce, Olivier; Bibi, Fehmida; Jiman-Fatani, Asif; Yasir, Muhammad; Helaby, Huda; Robert, Catherine; Fournier, Pierre-Edouard; Raoult, Didier
Abstract Oceanobacillus picturae is a strain of a moderately halophilic bacterium, first isolated from a mural painting. We demonstrate, for the first time, the culture of humanOceanobacillus picturae, strain S1T, whose genome is described here, from a stool sample collected from a 25-year-old Saoudian healthy individual. We used a slightly modified standard culture medium adding 100 g/L of NaCl. We provide a short description of this strain including its MALDI-TOF spectrum, the main identification tool currently used in clinical microbiology. The 3, 675, 175 bp long genome exhibits a G + C content of 39.15 % and contains 3666 protein-coding and 157 RNA genes. The draft genome sequence ofOceanobacillus picturae has a similar size to theOceanobacillus kimchii (respectively 3.67 Mb versus 3.83 Mb). The G + C content was higher compared withOceanobacillus kimchii (respectively 39.15 % and 35.2 %).Oceanobacillus picturae shared almost identical number of genes (3823 genes versus 3879 genes), with a similar ratio of genes per Mb (1041 genes/Mb versus 1012 genes/Mb). The genome sequencing ofOceanobacillus picturae strain S1 isolated for the first time in a human, will be added to the 778 genome projects from the gastrointestinal tract listed by the international consortium Human Microbiome Project.